1999
DOI: 10.1089/109065799316572
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tube Defect Prevalence in California (1990-1994): Eliciting Patterns by Type of Defect and Maternal Race/Ethnicity

Abstract: This study presents race/ethnicity-specific prevalence estimates of neural tube defects (NTDs) in California using 5 years of population-based data. NTD prevalence estimates include prenatally diagnosed cases, as well as cases diagnosed at birth. The California NTD Registry contains NTD case reports identified through the California Maternal Serum Alpha-Feto Protein (AFP) Screening Program, the California Birth Defects Monitoring Program, and additional reports from clinicians and clinics throughout the state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 20 publications
7
30
1
1
Order By: Relevance
“…(Table-I) Decreasing order of NTD's rates was for spina bifida (45.5%), anencephaly (31.7%), encephalocele (16.2%), holoproscecephaly (5.9%) and iniencephaly (Fig-5) (5.4%). which is compatible with study in Urmia (I.Abdi, 2008), as well as in California (Feuchtbaum LB,1999) [1], [2] As regards the subtypes of Anencephaly, Holoanencephaly were maximum followed by Meroanencephaly and Craniorachischisis and among spina bifida cases, meningomyelocele outnumbered those of meningocele and spina bifida occult as recorded from Table-II. (Fig-2,3,4) The lumbar region is more prone for spina bifida( Table-III [3], [ 4] As regards the consanguineous marriage, 11.63% of the affected group had a positive history. (Table IV [6], [7] While correlating the socio-economic status (Table V) [5], [8], [9], [10], [11] While correlating the maternal age with the occurrence of neural tube defects our observations show maximum number of cases in the age group of 20-24 years while anencephlic cases are mostly in women more than 30 years of age and spina bifida in mothers between age group of 20-24 years followed by the age group of more than 30 years which is in consonance with the study of I. Abdi (2008) and Sharada B. Menasinkai (2010) and Golalipour et al (2010) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(Table-I) Decreasing order of NTD's rates was for spina bifida (45.5%), anencephaly (31.7%), encephalocele (16.2%), holoproscecephaly (5.9%) and iniencephaly (Fig-5) (5.4%). which is compatible with study in Urmia (I.Abdi, 2008), as well as in California (Feuchtbaum LB,1999) [1], [2] As regards the subtypes of Anencephaly, Holoanencephaly were maximum followed by Meroanencephaly and Craniorachischisis and among spina bifida cases, meningomyelocele outnumbered those of meningocele and spina bifida occult as recorded from Table-II. (Fig-2,3,4) The lumbar region is more prone for spina bifida( Table-III [3], [ 4] As regards the consanguineous marriage, 11.63% of the affected group had a positive history. (Table IV [6], [7] While correlating the socio-economic status (Table V) [5], [8], [9], [10], [11] While correlating the maternal age with the occurrence of neural tube defects our observations show maximum number of cases in the age group of 20-24 years while anencephlic cases are mostly in women more than 30 years of age and spina bifida in mothers between age group of 20-24 years followed by the age group of more than 30 years which is in consonance with the study of I. Abdi (2008) and Sharada B. Menasinkai (2010) and Golalipour et al (2010) .…”
Section: Discussionsupporting
confidence: 87%
“…[2] Since strategies to modify women's dietary habits and vitamin use have achieved little progress.…”
Section: Introductionmentioning
confidence: 99%
“…As anencephaly is a fatal NTD type, only the average prevalence of spina bifida and encephalocele is considered, based on a share between respectively 47.5-59.3 % and 7.5-34.4 % of all NTDs. These figures are in line with studies in the United States (Feuchtbaum et al, 1999), Canada (Gucciardi et al, 2002;De Wals et al, 2007) and Ireland (FSAI, 2006). Based on the assumptions and input parameters of the DALY framework, such as the disability weights of the non-fatal NTD outcomes (Mathers et al, 1999) …”
Section: Annex 2 Global Burden Of Folate Deficiencysupporting
confidence: 89%
“…In particular, several studies have reported a somewhat higher than expected incidence of NTD in the Hispanic populations of California and Texas [Can®eld et al, 1996;Feuchtbaum et al, 1999;Barber et al, 2000]. A ®nding that a polymorphism conferring an increased risk of NTD is more common in Hispanics would be consistent with this observation.…”
Section: Discussionmentioning
confidence: 70%